Jigsaw learning model in increasing interest and learning of automotive electrical systems - Cecep Ardian; Subagyo Subagyo; Arif Bintoro Johan (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study was to determine the increase in interest in learningvand learning outcomes Automotive subjects Jigsaw cooperative learning model. This research is a class act. The data collection technique using observation, tests and questionnaires. The validity of the instrument in this study using the content validity using expert judgment. Data were analyzed using quantitative analysis techniques. The results showed that the application of cooperative learning model Jigsaw on the subjects of automotive electrical systems can increase interest and student learning outcomes in class XI SMK (Taman Karya) Tamansiswa Jetis Yogyakarta. Increased student interest in the first cycle an average of 59.04 (low) increased to 73.96 (currently) in the second cycle and increased again to 76.80 (high) in the third cycle. It can be concluded that Jigsaw cooperative learning model can improve learning outcomes interest and automotive electrical systems in class XI student of SMK (Taman Karya) Tamansiswa Jetis Yogyakarta.